2016
DOI: 10.1021/acs.cgd.6b00057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Decorating Titanium with Different Self-Assembled Monolayers on the Electrodeposition of Calcium Phosphate

Abstract: Calcium phosphate (CaP) ceramics are used in orthopedics and dentistry due to their excellent osseointegration and biocompatibility. The electrodeposition of CaP on titanium alloy covered with self-assembled monolayers (SAMs) was studied with respect to the influence of chain length, end-group charge, and anchoring group. SAMs with end-groups similar to the functional groups on the side chains of collagen were selected. This study is divided to three parts: (1) studying the effects of SAMs on the titanium subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
(134 reference statements)
0
9
0
Order By: Relevance
“…This oxide layer, typically several nanometres thick, is thermodynamically stable and repairs itself rapidly as long as there is low concentration (several ppm) of oxygen or water in the environment. However, because osseointegration of titanium implants takes a long time (typically three to six months), they are often coated with hydroxyapatite (HAp) and other calcium phosphates [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,23,27,28,29,30,31].…”
Section: Common Metallic Biomaterials and Their Corrosion Performancementioning
confidence: 99%
See 1 more Smart Citation
“…This oxide layer, typically several nanometres thick, is thermodynamically stable and repairs itself rapidly as long as there is low concentration (several ppm) of oxygen or water in the environment. However, because osseointegration of titanium implants takes a long time (typically three to six months), they are often coated with hydroxyapatite (HAp) and other calcium phosphates [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,23,27,28,29,30,31].…”
Section: Common Metallic Biomaterials and Their Corrosion Performancementioning
confidence: 99%
“…HAp and other CaP coatings provide enhanced osseointegration and fixation of orthopedic and dental implants [7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. In spite of the porous structure of many of these bioceramic coatings, it was reported that the corrosion resistance of CP-Ti could be improved by electrodepositing it with HAp, as long as the deposition conditions did not result in a too porous coating [12].…”
Section: Strategies For Corrosion Control In Vivomentioning
confidence: 99%
“…437 They used XPS and FTIR to confirm that the coating layer was connected to the titanium surface through intermolecular hydrogen bonds. 437 Moreover, Metoki et al 438 studied the calcium phosphate electrodeposition on a titanium alloy covered with SAMs regarding the chain length, end-group charge, and anchoring group. 438 They used ToF-SIMS to confirm that calcium-rich phases were formed primarily in the presence of SAMs.…”
Section: Chemical Surface Analysismentioning
confidence: 99%
“…Among these, the electrochemical technique is particularly attractive for efficiently coating highly irregular materials at ambient temperatures and has been already applied for metal substrates or porous carbon composites [1][2][3][10][11][12][13]. Additionally, the thickness of the coating and its chemical composition can be well controlled by setting adequate…”
Section: Introductionmentioning
confidence: 99%